2015
DOI: 10.1177/2056997115602991
|View full text |Cite
|
Sign up to set email alerts
|

From being bullied to being accepted: The lived experiences of a student with Asperger’s enrolled in a Christian university

Abstract: Thirteen participants from two private universities located in the western region of the United States shared their lived experiences of being a college student who does not request accommodations. In one's educational pursuit, bullying is often experienced. While the rates of bullying have increased, students with disabilities are more likely to be bullied. This article chronicles key incidents through the educational journey of a college student with Asperger's syndrome enrolled in a Christian university. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Carrington et al, 2003;Humphrey and Lewis, 2008;Huws and Jones, 2008). A more recent study in a Christian university setting confirmed the efficacy of phenomenology for research on the lived experience of a student with Asperger's syndrome (Reid, 2015). The data were collated and analysed using NVivo software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carrington et al, 2003;Humphrey and Lewis, 2008;Huws and Jones, 2008). A more recent study in a Christian university setting confirmed the efficacy of phenomenology for research on the lived experience of a student with Asperger's syndrome (Reid, 2015). The data were collated and analysed using NVivo software.…”
Section: Methodsmentioning
confidence: 99%
“…1.Although no longer a separate diagnostic category in the DSM-5 (American Psychiatric Association, 2013), Asperger’s syndrome and high-functioning autism are terms employed within the autism research literature reviewed in this paper (e.g. Reid, 2015). …”
mentioning
confidence: 99%